To Assess the Quality of Life of Women and the Effectiveness of Rehabilitation Who Suffered Massive Bleeding During Childbirth (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The clinical course of the postpartum period was studied prospectively in 203 women who suffered massive obstetric bleeding. The first, main group consisted of 109 women whose bleeding was stopped by surgical methods. The second, comparative group consisted of 94 women who had postpartum bleeding stopped by organ-preserving operations. The control group consisted of 50 women with uncomplicated course of labor and postpartum period. To determine the quality of life of women who suffered massive bleeding in childbirth, we used a questionnaire-MOS SF-36, consisting of 36 indicators.